Biodiversidad de Gorgojos (Curculionidae: Scolytinae) en teca (Tectona grandis) en Las Américas - González Tiban, Andrea Doria (2021)
The teak (Tectona grandis L.T.) is a forest species of economic importance for many countries worldwide. Its wood is highly appreciated and demanded for its quality. In cultivation there are a diverse entomofauna of beneficial organisms and those considered pests. Among these insects are the so-called scolithids belonging to the subfamily Scolytinae. The small beetles are classified into two large ecological groups, the bark beetles, and the ragweed beetles. The first are more specialized and carry out their development based on the feeding of the nutritional substances produced by the tree. The second group is characterized by being associated with symbiotic fungi, from which it obtains its food. Both groups are important in ecosystems because they are recyclers and some of these are considered important pests. The objective of this research was to compile information on the different genera that are related to the cultivation of teak in America. According to the information collected, it was determined that in all the countries where teak is grown, some genus of the scolithid group is present. The genera found were the following: Xyleborus, Xylosandrus, Euwallacea, Premnobius, Coccotrypes, Hypothenemus, Coptoborus, Xyleborinus, Trischidias, Cryptocarenus, Ambrosiodmus, Cnesinus, Araptus, Scolytus. Within the genera are the two ecological groups of scolithids, distributed in all the countries where teak is grown in America.